Effects of Corporate Social Responsibility in the Financial Performance of Commercial Banks in Embu County - Gatugi, Betty (University of Embu, 2019)
The objective of the study was to determine the effects of corporate social responsibility on the financial performance of commercial banks in Embu County.CSR activities are mainly carried out by the corporation with the aim of helping the society and pursuing of profits for growth. The corporations also gain an advantage from carrying out CSR activities though gaining of favorable public image. The banks also get advantages through customer retention .The study sought to determine the effects of CSR on financial performance on education health and environmental activities. The research aimed at finding out the effects of CSR activities in financial performance of commercial banks in Embu County since no other research on this has been done in Embu County. The stud) reviewed on the theories that explain the CSR activities such as Shareholders theory. Theory of social cost and the Agency theory. Data was obtained from commercial banks through questionnaires. There were 40 questionnaires that were provided to the 8 commercial banks where information was collected and out of 40 only 3 questionnaires were 'returned while other 9 que tionnaires were not returned by the respondents. Using descriptive research design the study tested the effects of corporate social responsibility on financial performance of commercial banks in Embu County. Data was analyzed using the statistical package for social sciences ( P version 22) and the result was presented using tables, graphs and figures. Financial performan e is the dependent variable while corporate social responsibility is the independent variables. The analysis showed that environmental activities were the most CSR activities carried out b) the commercial banks which had highest percentage of 67.7% of people 1 strongly agreed. The analysis showed that education activities were the second best who iti practiced in commercial banks with percentage of 35.5% and later the health activities with percentage of12.6% in commercial banks. The analysis indicated that most important advantage of carrying out the social responsibility activities was to enhance corporate image within the society. The stud) recommended that CBK should carry out audit on activities of commercial banks and to include their performance analysis in their database. The study showed that further studies should be made on effects of CSR activities in financial performance of MFIs